Interaction flow modeling language model-driven UI engineering of web and mobile apps with IFML - Brambilla, Marco 1976-; Fraternali, Piero (Elsevier, 2015)
"Learn how to apply model-driven techniques when designing the front end of applications with this introduction to the new OMG standard Interaction Flow Modeling Language (IFML)"--Provided by publisher